PRENATAL DEPRESSION’S IMPACT ON NEWBORNS AND LONG-TERM EFFECTS ON CHILD DEVELOPMENT - Olivera Agnes Adar (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background: Depression throughout pregnancy may be a drawback that's still under-addressed in midwifery services, so many studies have found that there is an influence between pregnancy depression on child development in the future. Objective: To understand prenatal depression’s impact on newborns and its long-term effects on child development from mothers who are depressed during pregnancy. Methods: The author used 10 reliable journals that discuss the impact of prenatal depression on birth outcomes and long-term effects on child development. Results: Several studies have additionally shown that prenatal depression has an effect on child development. The importance of paying attention to the mental health of mothers by partners, health workers, and the State is a preventive measure for children's health in the future. Conclusion: There are relationships between prenatal depression on child development, both emotional, behavioral, affective problems, physical growth, intelligence, neurobehavioral development, and other problems which can continue to affect their life. Besides, some studies suggest there is no relationship between prenatal depression and some developmental problems in children. It is better if health workers as doctors and midwives pay attention to the importance of maintaining the mental health of pregnant women as an initial preventive measure. Keywords: prenatal depression, newborns, child development.